Taxonomic significance of caryopsis in subfamily Panicoideae (Poaceae) using scanning electron microscopy and light microscopy. Issue 10 (29th June 2019) - Usma, Anwer; Ahmad, Mushtaq; Zafar, Muhammad; Ali, Muhammad I.; Kilic, Omer; Ozdemir, Fethi A.; Sultana, Shazia; Nazir, Abdul; Anjum, Farida; Kalsoom, Nomana
Abstract: In recent study, 13 taxa of subfamily Panicoideae were investigated for morphological characterization of caryopsis. Light microscope (LM) and scanning electron microscope (SEM) were utilized to study macro‐ and micro‐morphological caryopsis features respectively. Caryopsis size in studied taxa was recorded as 1.5–10 mm long and 1–4 mm wide. Caryopsis color was brown, green, yellow, and whitish‐brown. Caryopsis shape studied was obovate, elliptic, linear oblate, and round shallowly obtriangular. Hilum position is grooved and depressed. Caryopsis compression type was lateral and dorsiventral. Major variations among studied taxa were observed in terms of caryopsis surface pattern and epicuticular projection types. Six types of caryopsis surface pattern were observed viz. scabrate, rugose, striate, reticulate, papillate, and scabridulous. Structures such as silica cells, bulges, spines, prickles, granules, and bicellular microhair were studied as epicuticular projections. Major variations were observed among Cenchrus pennisetiformis and Cenchrus ciliaris as both has entirely two different types of surface patterns and epicuticular projections. Anticlinal wall thickness and pattern as well as periclinal wall texture and level were investigated. The present research work emphasized on caryopsis characterization of subfamily Panicoideae and it is recommended to establish phylogeny within subfamily Panicoideae and with other subfamilies of Poaceae. Abstract : Quantitative characters of caryopsis as length, width and weight Macro‐morphological features of caryopsis including color, shape, hilum, stylopodium and compression Micro‐morphological features of caryopsis such as epicuticular projections, surface patterns and wall patterns Taxonomic key to show relationship among Panicoideae species based on caryopsis features